Inhaled Therapy-Associated Adverse Reactions in Obstructive Respiratory Diseases - Fonseca, Willy Anselmo Ribeiro (2019)
Introduction: Obstructive lung diseases (OLDs) include asthma, chronic obstructive pulmonary disease (COPD), and asthma/COPD overlap (ACO). OLDs therapy includes medications that are administered through inhalation devices belonging to the following classes: corticosteroids, ?2-adrenergic receptor agonists and muscarinic receptor antagonists. Certain adverse drug reactions (ADRs) associated with this therapy have been reported in pre-marketing clinical trials and case reports. However, there are few post-marketing surveillance studies focused on suspected ADRs spontaneously reported to the Pharmacovigilance system, and none has been published in Portugal. Objectives: To characterise spontaneous reports (SRs) of suspected ADRs associated with OLDs inhaled therapy received by the Portuguese Pharmacovigilance System (PPS), from 2007 to 2017. Materials and methods: Retrospective observational study based on the analysis of suspected ADRs spontaneously reported to the PPS, associated with 20 inhalers of the following classes: LAMA (long-acting muscarinic antagonists), SAMA (short acting muscarinic antagonists), SABA (short-acting ?2 agonists) and LABA (long-acting ?2 agonists), ICS (inhaled corticosteroids), LAMA / LABA combination, SAMA / SABA combination and ICS / LABA combination. SRs were evaluated according to the demographic characteristics of the patients, pharmacological classes of suspected drugs, type and seriousness of suspected ADRs. Results: 230 SRs were analysed, accounting for a total of 599 suspected ADRs. There was a trend towards an increase in the number of notifications over the years under study, with the average being 2 SRs per 1000 inhabitants with one OLD per year. The ICS/LABA combination obtained the highest frequency in both SRs (n = 74, 32.2%) and in ADRs (n = 196, 32.7%). There was a slight predominance in men (SR n = 118, 51.3%) and non-elderly adults were the most affected age group (SR n = 90, 39.1%). The majority of SRs were classified as being serious (n = 162, 70.4%). In total, "respiratory, thoracic and mediastinal diseases" ADRs were the most reported ones (n = 117, 19.5%), with "dyspnoea" being the most frequent one (n = 29; 4.8%). There were many cases of medication errors associated with symptoms and exacerbations, and also cases of SABAs overdose. Conclusions: Most of the SRs were associated with controller medications and classified as being serious. Most of the reactions were expected, with the authorities' recommendation being to review those not expected to update the drug safety profile. The present data confirm the existence of errors in the use of inhalation devices, which are associated with suboptimal levels of therapeutic effect and, therefore, ineffective control of the diseases. The data also indicate the existence of overuse of relieving medication.